Paranormal: Mengurai Sanad Hadist Tentang Supranatural - Zen Amrullah (HUMANISTIKA : Jurnal Keislaman, 2016)
Indonesia is a fertile place for shamanism. This country seems shackled by shamanism. Just sell the land must go to the shaman, want his business to run smoothly, want his position to survive, want to have the authority and feared subordinates must go to the shaman. In this discussion will be focused on the Islamic view in the hadith of the Prophet Muhammad SAW about the beliefs of people who come to paranormal, because if they are wrong perceptions then this will ration their faith in Allah and His messengers. This research is a library research.